2021
DOI: 10.1021/acsomega.1c03418
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Rate of Hydrothermal Ammonia Production from Chicken Manure

Abstract: Ammonia is an important fertilizer feedstock and an expected next-generation hydrogen carrier. Thus, it is necessary to ensure effective production of ammonia from the waste biomass. In this regard, chicken manure was treated in an autoclave under hydrothermal reaction conditions, and the ammonia release rate was determined in the temperature range of 250–400 °C for holding times ranging from 2 to 120 min. A reaction network for ammonia production was proposed, and the reaction rate constants were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Figure A represents N rec in different phases from the HTL of chicken manure. From the figure, it becomes evident that most of the N was dispersed into AP typically in the ammonium or organic-N form . Such N distribution can be supported by a previous study by Lu et al, where most of the N was partitioned into AP (∼45% N rec ) followed by oil (∼22% N rec ) and gas phase (∼18% N rec ), with hydrochar having least N rec .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Figure A represents N rec in different phases from the HTL of chicken manure. From the figure, it becomes evident that most of the N was dispersed into AP typically in the ammonium or organic-N form . Such N distribution can be supported by a previous study by Lu et al, where most of the N was partitioned into AP (∼45% N rec ) followed by oil (∼22% N rec ) and gas phase (∼18% N rec ), with hydrochar having least N rec .…”
Section: Resultssupporting
confidence: 75%
“…From the figure, it becomes evident that most of the N was dispersed into AP typically in the ammonium or organic-N form. 59 Such N distribution can be supported by a previous study by Lu et al, 15 where most of the N was partitioned into AP (∼45% N rec ) followed by oil (∼22% N rec ) and gas phase (∼18% N rec ), with hydrochar having least N rec . In addition, Ekpo et al also found similar results where almost 50% N rec was observed in the AP from HTL (at 250 and 350 °C) of chicken manure at 60 min reaction time.…”
Section: N Recovery (N Rec ) 3221 Direct-htlsupporting
confidence: 58%
“…It is important to note that such technologies have high potential because, for example, the technology can, for the first time, ensure the production of ammonia cheaper than when using the Haber-Bosch process. In addition to anaerobic fermentation, there were other methods of obtaining ammonia from livestock waste, for example, using Escherichia coli [15] or using a hydrothermal approach [16]. However, they probably use not fewer resources than the traditional ammonia production approach.…”
Section: Resultsmentioning
confidence: 99%